Alphacoronaviruses in New World Bats: Prevalence, Persistence, Phylogeny, and Potential for Interaction with Humans - Osborne, Christina; Cryan, Paul M.; O'Shea, Thomas J.; Oko, Lauren M.; Ndaluka, Christina; Calisher, Charles H.; Berglund, Andrew D.; Klavetter, Mead L.; Bowen, Richard A.; Holmes, Kathryn V.; Dominguez, Samuel R. (PloS one, 2011)
Bats are reservoirs for many different coronaviruses (CoVs) as well as many other important zoonotic viruses. We sampled feces and/or anal swabs of 1,044 insectivorous bats of 2 families and 17 species from 21 different locations within Colorado from 2007 to 2009. We detected alphacoronavirus RNA in bats of 4 species: big brown bats (Eptesicus fuscus), 10% prevalence; long-legged bats (Myotis volans), 8% prevalence; little brown bats (Myotis lucifugus), 3% prevalence; and western long-eared bats (Myotis evotis), 2% prevalence. Overall, juvenile bats were twice as likely to be positive for CoV RNA as adult bats. At two of the rural sampling sites, CoV RNAs were detected in big brown and long-legged bats during the three sequential summers of this study. CoV RNA was detected in big brown bats in all five of the urban maternity roosts sampled throughout each of the periods tested. Individually tagged big brown bats that were positive for CoV RNA and later sampled again all became CoV RNA negative. Nucleotide sequences in the RdRp gene fell into 3 main clusters, all distinct from those of Old World bats. Similar nucleotide sequences were found in amplicons from gene 1b and the spike gene in both a big-brown and a long-legged bat, indicating that a CoV may be capable of infecting bats of different genera. These data suggest that ongoing evolution of CoVs in bats creates the possibility of a continued threat for emergence into hosts of other species. Alphacoronavirus RNA was detected at a high prevalence in big brown bats in roosts in close proximity to human habitations (10%) and known to have direct contact with people (19%), suggesting that significant potential opportunities exist for cross-species transmission of these viruses. Further CoV surveillance studies in bats throughout the Americas are warranted.